2004
DOI: 10.1074/jbc.m400673200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoprotein of the Rinderpest Virus Forms a Tetramer through a Coiled Coil Region Important for Biological Function

Abstract: Phosphoprotein (P) of negative sense RNA viruses functions as a transcriptional transactivator of the viral polymerase (L). We report here the characterization of oligomeric P protein of rinderpest virus (RPV) and provide a structural basis for its multimerization. By size exclusion chromatography and dynamic light scattering analyses we show that bacterially expressed P protein exists as an oligomer, thus excluding the role of phosphorylation in P protein oligomerization. Gel filtration analyses of various pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
31
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 42 publications
4
31
0
Order By: Relevance
“…Consistent with this conclusion, it was reported that the inactive monomeric P protein of human parainfluenza virus type 3 maintains its ability to bind to its L protein (11). Similar data have been published for rinderpest virus belonging to the family Paramyxoviridae, although the oligomerization-incompetent P protein did not support transcription, but it still bound to its L protein (41). However, a different situation was reported for Marburg virus, which belongs to the family Filoviridae, in which monomeric VP35 (a counterpart of P protein) fails to interact with its RNA polymerase L (35).…”
Section: Discussionsupporting
confidence: 75%
“…Consistent with this conclusion, it was reported that the inactive monomeric P protein of human parainfluenza virus type 3 maintains its ability to bind to its L protein (11). Similar data have been published for rinderpest virus belonging to the family Paramyxoviridae, although the oligomerization-incompetent P protein did not support transcription, but it still bound to its L protein (41). However, a different situation was reported for Marburg virus, which belongs to the family Filoviridae, in which monomeric VP35 (a counterpart of P protein) fails to interact with its RNA polymerase L (35).…”
Section: Discussionsupporting
confidence: 75%
“…This result suggests that only complexes composed of functional VP35 proteins are able to support transcription and replication. Further support for this idea comes from results published by Rahaman et al showing that homo-oligomerization-competent but functionally negative mutants of the rinderpest virus P protein display a dominant-negative phenotype (37). Possibly, this feature can be addressed in the quest to develop antivirals against MARV.…”
Section: Discussionmentioning
confidence: 53%
“…In the present study, we confirmed that all P domains are required for full P function. P multimerization has been found to be essential for viral transcription of rinderpest virus and VSV (10,19). Interestingly, when MuV P truncations lacking either the N-terminal domain (P OC ) or the C-terminal domain (P NO ) were transfected together, P activity was restored due to trans-complementation through P O .…”
Section: Discussionmentioning
confidence: 93%
“…The self-association of P is required for transcriptional activity, and the binding site for SeV L was found to neighbor the oligomerization region (5,(7)(8)(9). Tetrameric P structures have also been observed for other paramyxoviruses, with crystallization of the P oligomerization domains being found for measles virus, human metapneumovirus, and mumps virus (10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 84%